Mobile learning: o aprendizado do século XXI - Cônsolo, Angeles Treitero García (2008)
Since the appearance of Internet with the WWW (World Wide Web), resources do not stop to emerge and expand new paths to information. Today, we are living a new stage with the emergence of mobile media, the collective mobile computers (CCM) settle down with the mobile computing ubiqua. This is resources that include devices such as: cellular, PDAs (Personal Digital Assistance), MP3, MP4, palm-tops, pagers, games etc. Those equipments included us in real time to join into the information society, be connected its a part of our existence. Many things are making with the mobile device such as art, music, sounds, new forms of social control, and much more. However, we don t forget they are producing a new language, a new look at art and the culture, a new form to learn and teach. In that context, this research is focused in the device mobile and how they help to develop cognitive structures in the formal and inform learning. To achieve this goal, in the first chapter we ll discute the main learning theories and how and how each theoretical analyses the studies relating the cognitive processes. In the second chapter, we ll study the mobile device and yours specific concepts such as, interactivity, ubiquity, interconnection between networks on and offline, nomadism, etc. So we ll to present where they are inserted both in society and scientific studies. Finally, in the third chapter, seeks to realize the synthesis reflexive between the previous chapter. In this chapter we ll be the selection theory learning which has more syntony with the cognitive potential of mobile device united with the transformations reflections in the learning theories because the new technologies. So, the theoretical foundation is based in the contributions of some theories constructivists selected because the learning is knowledge process, relationships understanding whose the external conditions act mediated to internal condition. For this, sociocultural theory of development and learning or Vygotsky s theory mediation and Piaget s theory development cognitive. The study concerning to mobiles devices be based on dedicated researchers to creation and search in the mobile area such as Giselle Beiguelman, Lucia Santaella, André Lemos, among others. The methodology is exploratory, based bibliographic data. The empirical research geared towards the selections Theoretical data act in the learning process, develop cognitive structures and scientist s mobile device. This is the bases the reflections concerning the mobile contributions can to bring for the learning